2017
DOI: 10.17235/reed.2017.5087/2017
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of endoscopic radiofrequency ablation for the treatment of dysplastic Barrett’s esophagus in Spain

Abstract: Background and study aims: To assess the cost-effectiveness of introducing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…A cost–utility analysis also compared RFA with endoscopic surveillance over 15 years and showed that RFA was cost effective at a threshold of £20 000 per QALY gained. 68 …”
Section: Consultationmentioning
confidence: 99%
See 3 more Smart Citations
“…A cost–utility analysis also compared RFA with endoscopic surveillance over 15 years and showed that RFA was cost effective at a threshold of £20 000 per QALY gained. 68 …”
Section: Consultationmentioning
confidence: 99%
“…In addition to the clinical studies, four cost–utility analyses were identified. 68 76–78 They reported that at a threshold of £20 000 per QALY gained, EMR combined with RFA was cost effective versus endoscopic surveillance 77 ; EMR plus RFA plus surveillance, EMR plus APC plus surveillance and surgery were all cost effective versus no surveillance 78 ; RFA followed by endoscopic surveillance was cheaper and more effective than oesophagectomy 76 ; and RFA alone was cheaper and more effective than oesophagectomy. 68 …”
Section: Consultationmentioning
confidence: 99%
See 2 more Smart Citations